Design, Development and Implementation of a Master ofScience Program for Chemical and Nuclear Engineering:Integration of CAPE (Modelling, Simulation and Control) Skills - Goryunov A. G. Aleksey Germanovich; Dyadik V. F. Valery Feodosievich; Liventsov S. N. Sergey Nikolaevich; Kozin K. A. Kirill Andreevich; Manenti F. Flavio; Pierucci S. Sauro (2015, 2015)
Title screen